Ethics and AI-Plagiarism in an Academic Environment: Students' Understanding of Compliance with Author's Ethics and the Problem of Plagiarism in the Process of Interaction with Generative Artificial Intelligence - P. V. Sysoyev (Moscow Polytechnic University, 2024)
Everyday, artificial intelligence (AI) is being increasingly integrated into the teaching and learning process at Russian universities. The high level of quality of feedback from AI tools leads to the spread of AI plagiarism - unauthorized borrowing of generative AI materials - among students. The purpose of this study is to: a) highlight aspects that determine students' understanding of the issues of compliance with author's ethics and the problem of plagiarism when interacting with generative AI; b) develop a questionnaire to determine students' understanding of the issues of compliance with author's ethics and the problem of AI plagiarism; c) conduct an online survey of university students, analyze and discuss the results obtained. The paper highlights five aspects that determine students' understanding of the issues of compliance with author's ethics and the problem of AI plagiarism when completing educational assignments and preparing research texts: a) students' general understanding of the issues of compliance with author's ethics and the problem of plagiarism in an academic environment; b) students' experience of AI tools for educational purposes; c) students' understanding of the problem of AI plagiarism and attitude towards borrowing materials from generative AI; d) teachers' actions to prevent AI plagiarism among students; e) the policy of educational organizations regarding student compliance with ethics and AI plagiarism. An online questionnaire was developed to determine the degree to which students understand the issues of compliance with copyright ethics and the problem of AI plagiarism. 1,599 students from 29 universities of the Russian Federation took part in the survey. The results showed that in general, in the Russian student community, plagiarism is a widespread social phenomenon, many types of which are perceived by young people as a norm of academic behavior. Despite the relatively high awareness of students in the field of AI technologies, the extremely rare use by teachers of specialized subject disciplines of AI tools in the educational process I'd the reason for the current low level of spread of AI plagiarism in the academic environment. At the same time, it is necessary to state that students lack a systematic understanding of exactly how they can "legally" use generative AI materials and what exactly will be considered AI plagiarism. According to students, the importance of understanding the issues of compliance with author ethics and the problem of AI plagiarism will depend, on the one hand, on the actions of teachers to explain to students the rules for using generative AI materials, and on the other hand, the presence in universities of a regulatory framework regulating the field and the extent to which students use AI in the educational process.